IMPLEMENTATION OF THE FLIPPED CLASSROOM LEARNING MODEL TO DETERMINE STUDENTS' MATHEMATICAL SPATIAL ABILITY ON CUBE AND BLOCK MATERIAL IN GRADE VIII SMP - Watratan, Yoseph; Laurens, Theresia; Ayal, Carolina Selfisina (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2024)
This study aims to determine the implementation of the flipped classroom model in mathematics learning on the building materials of flat side spaces, cubes and blocks on students' spatial mathematical ability. The type of research used is quantitative Data collection method using observation sheets, tests, interviews, and documentation. The data were analyzed using quantitative descriptive and simple linear regression with prerequisite tests consisting of normality test and linearity test. The results of this study show that the implementation of the flipped classroom learning model is on very good criteria, with the average percentage of 4 meetings being 95%. The students' high mathematical spatial ability exceeded the minimum completeness criteria by 86% in the good category, judging from the 28 students who took the test, 24 students had completely exceeded the KKM. The implementation of the flipped classroom learning model has an effect on students' mathematical skills with a significance value of 0.000. The implementation of the flipped classroom learning model can improve students' mathematical spatial skills. This can be seen from the results of the final test of students who participated in the learning process. The use of WhatsApp groups and learning videos as a medium of communication and a source of learning for students at home. Learning in the classroom through assignment presentations and group discussions